Development and Implementation of a Multicultural-Based Learning Model to Enhance Understanding of Cultural Diversity - Djafar, Nurlia; Djafri, Novianty (PPSDP International Journal of Education, 2024)
This research aims to develop and implement an effective multicultural-based learning model to enhance the understanding of cultural diversity among students of the Department of Dance and Theater, Faculty of Arts and Culture, Universitas Negeri Gorontalo in the course of Indonesian Dance. In the era of globalization, understanding cultural diversity becomes important to build tolerance and appreciation for differences. The research method used is a qualitative approach with a classroom action research design involving 30 students. The research procedure consists of the preparation, implementation, and evaluation stages, which include the use of questionnaires, interviews, and observations to collect data. The research results show that the implementation of a multicultural-based learning model significantly enhances students’ understanding of cultural diversity, as evidenced by the increase in questionnaire scores and active student participation during the learning process. This research concludes that this learning model can be an effective strategy in teaching cultural diversity through dance, as well as making a positive contribution to the development of the curriculum in the Performing Arts department.